Incidence of recreational techniques to reduce attrition and improve learning English as a second language on students of elementary and pre-intermediate levels at Lincoln College of foreign languages Institute during april july 2008 - Dávila Herrería, Juan Carlos (2008)
To do this research, I have followed a scheme proposed by The Army Polytechnic School Language Department which clearly specifies step by step each detail of how to develop a research and obtain the requirement results which permit me to complete it successfully, without forgetting the unconditional support of my dear tutors. First of all, I selected the subject to be investigated which was not difficult for me, as a student, I have had experiences in the English teaching learning process during my studies at school, besides I have worked at Lincoln College of Foreign Languages Institute as a regular teacher. Along my job as an English teacher, I have found some negative aspects in the development of English classes which gave me a trace to start the first step of my research. Through observation and suggestion of some colleagues and specialists, it was possible to select this interesting subject which affects the student s life and learning The main subject is: incidence of recreational techniques to reduce attrition and improve learning English as a second language. Immediately I started to find out the primary and secondary sources which let me understand this subject much better and have good arguments to do the theoretical framework in which I supported my research.